Recommendations for prenatal echocardiography: a report from international prenatal cardiology collaboration group. - Murlewska, Julia; Słodki, Maciej; Axt-Fliedner, Roland; Rizzo, Giusseppe; Sklansky, Mark; Weiner, Stuart; Blickstein, Isaac; Respondek-Liberska, Maria (Prenatal Cardiology, 2017)
International Prenatal Cardiology Collaboration Group (IPCCG) links specialists from prenatal cardiology all over the world. In this recommendation we would like to focus on the fetal/prenatal echocardiography official report. So far many recommendations focused mainly on technical aspects of the fetal heart examination.